An Experimental Study on the Effect of Temperature on Piezoelectric Sensors for Impedance-Based Structural Health Monitoring - Baptista, Fabricio G. [UNESP]; Budoya, Danilo E. [UNESP]; Almeida, Vinicius A. D. de [UNESP]; Ulson, Jose Alfredo C. [UNESP] (Mdpi Ag, 2014)
The electromechanical impedance (EMI) technique is considered to be one of the most promising methods for developing structural health monitoring (SHM) systems. This technique is simple to implement and uses small and inexpensive piezoelectric sensors. However, practical problems have hindered its application to real-world structures, and temperature effects have been cited in the literature as critical problems. In this paper, we present an experimental study of the effect of temperature on the electrical impedance of the piezoelectric sensors used in the EMI technique. We used 5H PZT (lead zirconate titanate) ceramic sensors, which are commonly used in the EMI technique. The experimental results showed that the temperature effects were strongly frequency-dependent, which may motivate future research in the SHM field.
Keywords: piezoelectric sensors; PZT; structural health monitoring; SHM; electromechanical impedance; EMI; temperature